Eggs coating machine for salted egg small medium enterprise (SMEs) - Nur Hidayah Binti Mat Noh (School of Manufacturing Engineering, University Malaysia Perlis, 2016)
Eggs coating machine to design for user especially to SME industries. The product is designed to produce the salted egg in 16000 pieces per day.This machine have three aspects that should be taken into consideration to implement this design; egg movement processin, egg place coating with clay and burned paddy husk. The mechanisms of this eggs coating machine is created to design by refering the methods of using Quality function deployment (QFD), morphology method, pugh;s method, computer aided design and computer aided engineering (CAE).